ANALISIS KESULITAN SISWA KELAS IV DALAM MEMAHAMI MATERI PENGUKURAN MATEMATIKA DI SDN 262 PANYILEUKKAN CIBIRU - Siti Widiana, Amelia (Jurnal Edumatic: Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the forms and causal factors of learning difficulties experienced by fourth-grade elementary students in understanding measurement concepts, specifically volume and time. The research used a descriptive qualitative approach, with data collected through questionnaires and interviews. The subjects were 26 fourth-grade students at SDN 262 Panyileukkan Cibiru and one classroom teacher. The results indicated that most students had difficulties in converting measurement units, using measuring tools, and reading or determining time. These difficulties stem from the limited use of concrete media and the lack of contextual learning methods relevant to students’ daily experiences. The findings highlight the importance of implementing learning strategies that are based on direct experiences, use of instructional tools, and communicative approaches in Mathematics instruction. This study provides valuable insights for developing adaptive teaching methods that accommodate the cognitive development of elementary school students.